Dispersal of a nearshore marine fish connects marine reserves and adjacent fished areas along an open coast. Issue 7 (13th April 2019) - Baetscher, Diana S.; Anderson, Eric C.; Gilbert‐Horvath, Elizabeth A.; Malone, Daniel P.; Saarman, Emily T.; Carr, Mark H.; Garza, John Carlos
Abstract: Marine species with pelagic larvae typically exhibit little population structure, suggesting long‐distance dispersal and high gene flow. Directly quantifying dispersal of marine fishes is challenging but important, particularly for the design of marine protected areas (MPAs). Here, we studied kelp rockfish ( Sebastes atrovirens ) sampled along 25 km of coastline in a boundary current‐dominated ecosystem and used genetic parentage analysis to identify dispersal events and characterize them, because the distance between sedentary parents and their settled offspring is the lifetime dispersal distance. Large sample sizes and intensive sampling are critical for increasing the likelihood of detecting parent–offspring matches in such systems and we sampled more than 6, 000 kelp rockfish and analysed them with a powerful set of 96 microhaplotype markers. We identified eight parent–offspring pairs with high confidence, including two juvenile fish that were born inside MPAs and dispersed to areas outside MPAs, and four fish born in MPAs that dispersed to nearby MPAs. Additionally, we identified 25 full‐sibling pairs, which occurred throughout the sampling area and included all possible combinations of inferred dispersal trajectories. Intriguingly, these included two pairs of young‐of‐the‐year siblings with one member each sampled in consecutive years. These sibling pairs suggest monogamy, either intentional or accidental, which has not been previously demonstrated in rockfishes. This study provides the first direct observation of larval dispersal events in a current‐dominated ecosystem and direct evidence that larvae produced within MPAs are exported both to neighbouring MPAs and to proximate areas where harvest is allowed.